A blueprint for research on Shankopathies: A view from research on autism spectrum disorder. Issue 2 (17th December 2013) - Carbonetto, Salvatore; Carbonetto, Salvatore; Bourgeron, Thomas
ABSTRACT Autism spectrum disorders (ASD) are associated with mutations in a host of genes including a number that function in synaptic transmission. Phelan McDermid syndrome involves mutations in SHANK3 which encodes a protein that forms a scaffold for glutamate receptors at the synapse. SHANK3 is one of the genes that underpins the synaptic hypothesis for ASD. We discuss this hypothesis with a view to the broader context of ASD and with special emphasis on highly penetrant genetic disorders including Shankopathies. We propose a blueprint for near and longer‐term goals for fundamental and translational research on Shankopathies. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 85–112, 2014